Evangelical Christian women : war stories in the gender battles - Ingersoll, Julie (Qualitative studies in religion., 2003)
Evangelical Christian Women draws on two years of ethnographic research nationwide to shed new light on the gender conflict faced by women in evangelical Christianity. Julie Ingersoll goes beyond previous attempts to find avenues of empowerment for fundamentalist women to offer a more nuanced look at the challenges they face when they occupy positions of leadership which violate traditional gender norms. She looks where other studies do not--at women who, while remaining entrenched in and committed to evangelical Christianity, are also resisting accepted gender roles. Evangelical Christian Wome.